2013
DOI: 10.1002/clc.22144
|View full text |Cite
|
Sign up to set email alerts
|

A Review on State‐of‐the‐Art Data Regarding Safe Early Discharge Following Admission for Pulmonary Embolism: What Do We Know?

Abstract: Background Although most patients with acute pulmonary embolism (PE) remain hospitalized during initial therapy, some may be suitable for partial or complete outpatient management, which may have a significant impact on healthcare costs. Hypothesis This article reviews the state‐of‐the‐art data regarding recognition of very‐low‐risk PE patients who are potentially eligible for outpatient treatment, along with the safety, management, and cost‐effectiveness of this strategy. We propose an algorithm based on coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 69 publications
0
15
0
1
Order By: Relevance
“…Low-risk patients may be eligible for outpatient treatment with heparin or novel oral anticoagulants. 15 25 Meta-analyses, systematic reviews and a large clinical trial support the safety of this approach 15 26 27. Piran et al 26 found that selected patients with PE treated as outpatients had low rates of recurrent venous thromboembolism (VTE) (1.47%), fatal PE (0.47%) and major bleeding (0.81%), and Vinson et al 28 found that outpatient treatment was associated with low 90-day VTE-related mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Low-risk patients may be eligible for outpatient treatment with heparin or novel oral anticoagulants. 15 25 Meta-analyses, systematic reviews and a large clinical trial support the safety of this approach 15 26 27. Piran et al 26 found that selected patients with PE treated as outpatients had low rates of recurrent venous thromboembolism (VTE) (1.47%), fatal PE (0.47%) and major bleeding (0.81%), and Vinson et al 28 found that outpatient treatment was associated with low 90-day VTE-related mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Despite many prognostic model have been proposed, such as the ESC prognostic model, the original and sPESI score, the Geneva prognostic model, the LR-PED, the HESTIA criteria, the Spanish score and other, which is the best prognosticator for the identification of 30-days mortality in PE patients in real world remains unclear. 4,5,9,10,[17][18][19][20] Moreover, the majority of the proposed prognostic models focus only on early mortality risk without bleeding risk stratification. On the other hand, few bleeding risk scores have been proposed, but, anyway, these do not give information about PE-related early mortality risk.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Many prognostic models for risk stratification of acute PE have been proposed, but which is the best prognosticator remains unclear, especially in daily real practice. 4 In 2008 for the first time, the European Society of Cardiology proposed a model based on hemodynamics and cardiac biomarkers. 5 This model has represented a cornerstone in acute management of PE.…”
Section: Introductionmentioning
confidence: 99%
“…Several scores have been developed (and were recently reviewed 33 ) to assess PE patients' risk for poor outcome in the weeks after the PE diagnosis, but most were not developed for the determination of whom to treat on an outpatient or inpatient basis, but rather as tools to assess risk of good or poor outcomes from the PE. The HESTIA criteria, recently evaluated in a multicenter prospective cohort study, were developed for inpatient/outpatient management decisions and use common sense parameters to determine hospital admission need 34 ( Table 2).…”
Section: Outpatient Versus Inpatient Managementmentioning
confidence: 99%